EXPLORING CHATGPT IN LANGUAGE EDUCATION: FRIEND OR FOE FOR TEACHERS? - Rosdiana; Mulyadi Syahputra (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Amidst the rapid progress in artificial intelligence, especially with the emergence of ChatGPT, there is a growing interest among experts and practitioners. This research delves into the perspectives of language educators in Indonesia concerning ChatGPT's potential as a language learning tool and the associated concerns. The study adopts a quantitative approach, employing an online questionnaire featuring 18 items rated on a four-point Likert scale and three open-ended queries. The sample encompasses 100 educators, English, Indonesian, and Mandarin language teachers and lecturers. Results reveal that a significant number of respondents are acquainted with internet-based artificial intelligence, acknowledging the practicality of ChatGPT in educational settings. Notably, 87% of language educators express support for initiatives aimed at enhancing understanding and integration of Artificial Intelligence in Education (AIEd) to improve instructional efficiency. Furthermore, a majority believes that ChatGPT can assist language learners in refining vocabulary, grammar, oral, and written skills. These findings underscore the importance for educational stakeholders to find a balanced approach between integrating AI tools and maintaining a pedagogical paradigm that prioritizes student engagement and critical cognitive development.